The relationship of various risk factors to the incidence of Herpes Zoster at PKU Muhammadiyah Gamping Hospital - Rencani, Nadia; Estri, Siti Aminah Tri Susila (Science Midwifery, 2024)
Shingles (HZ) is reactivation of the Varicella zoster virus which is characterized by dermatomal vesicular lesions and unilateral pain. HZ cases have increased in recent decades, especially in people with weak immune systems, such as the elderly and women. To determine the relationship between various risk factors and the incidence of HZ at PKU Muhammadiyah Gamping Hospital in 2020 – 2022. Analytical observational research method with a cross-sectional design. Data source from medical records of PKU Muhammadiyah Gamping Hospital in 2020 - 2022 using total sampling method. The research subjects were HZ patients. Cases of contact dermatitis were used as a comparison. The number of HZ patients >64 years (31.2%), women (57.5%), with diabetes (9.7%), hypertension (22.1%), asthma (1.9%), heart disease (5 .2%), and other skin diseases (26%). There was a relationship between age (p=0.00), diabetes (p=0.03), hypertension (p=0.00), and other skin diseases (p=0.00) with HZ. There was no relationship between gender (p = 0.10), asthma (p = 0.68), heart disease and HZ (p = 1.00).Age, diabetes, hypertension, and other skin diseases were significantly associated with HZ, whereas gender, asthma, and heart disease were not associated with HZ.